The Effect of Management Design on the Portfolio Concentration and Performance of Mutual Funds. Issue 4 (1st July 2016) - Goldman, Eitan; Sun, Zhenzhen; Zhou, Xiyu (Thomas)
Abstract : We show that the performance of actively managed equity mutual funds increases when portfolios are concentrated in the top one or two stocks within each industry sector. Funds managed by a single manager have much more concentrated portfolios, tend to perform better, and have higher expense ratios than funds managed by multiple managers. We observe that when a fund's management design is changed from single manager to multiple managers, the portfolio's within- and cross-sector concentration, performance, and expense ratios decrease. Abstract : Editor's note: This article was reviewed and accepted by Robert Litterman, executive editor at the time the article was submitted. Editor's note: This article was reviewed via our double-blind peer review process. When the article was accepted for publication, the authors thanked the reviewers in their acknowledgments, and the reviewers were asked whether they agreed to be identified in the authors' acknowledgments. Robin Braun and Joseph Chen were the reviewers for this article.